2016
DOI: 10.1186/s40795-016-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phytate intake inhibits the bioavailability of iron and calcium in the diets of pregnant women in rural Bangladesh: a cross-sectional study

Abstract: Background: Phytate, a potent inhibitor of calcium, iron, and zinc absorption, may hamper the bioavailability of these micronutrients at the time of pregnancy. This study assessed dietary phytate intake and its inhibitory effect on the bioavailability of calcium, iron, and zinc from the diets of pregnant women in rural Bangladesh. The study also explored significant determinants that predicted the absorption of these minerals from the diet. Methods: A multiple pass recall (MPR) approach was used for this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 51 publications
(77 reference statements)
1
61
1
5
Order By: Relevance
“…Most notably, Fe and Zn deficiencies occur due to high phytate intake. Negative effects of PA (mainly low mineral bioavailability) have a significant impact on infants and pregnant and lactating women if their diet contains ample amounts of cereal‐based food . PA is also reported to have some beneficial roles as plant antioxidant and protector of seeds during oxidative stress .…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, Fe and Zn deficiencies occur due to high phytate intake. Negative effects of PA (mainly low mineral bioavailability) have a significant impact on infants and pregnant and lactating women if their diet contains ample amounts of cereal‐based food . PA is also reported to have some beneficial roles as plant antioxidant and protector of seeds during oxidative stress .…”
Section: Introductionmentioning
confidence: 99%
“…The slight decrease of phytate levels from 6 weeks of storage is probably related to the capacity of endogenous phytates to be metabolized on incubation. Al Hassan et al (2016) in their study of phytate in diets of pregnant women concluded that phytate is the strongest inhibitory predictor of mineral bioavailability as it is significantly associated with bioavailability of calcium, iron and zinc from diet.…”
Section: Phytatementioning
confidence: 99%
“…High-phytate diets cause stronger adverse effects on Ca 2+ , iron, and zinc levels among infants, young children, and pregnant and lactating women when cereal-based foods represent a large percentage of the diet (Al Hasan et al, 2016; Chan et al, 2007). Prior studies of dogs demonstrate that increasing the levels of phytate reduces the intestinal absorption of Ca 2+ and causes nutritional rickets (Harrison and Mellanby, 1939; Mellanby, 1949).…”
Section: Introductionmentioning
confidence: 99%